Alterations in the Gut Microbiome of Infants Consuming Partially Hydrolyzed Cow Milk Protein Formula - Gilley, Stephanie (Curr Dev Nutr, 2021)
OBJECTIVES: The first year of life is a critical window for appropriate enteric microbiome development. Variations in infant diets have persistent effects on gut microbial ecology. Compared to intact protein formulas (IPF), partially hydrolyzed infant formulas (PHF) contain broken down milk proteins and may impact development of atopic conditions in high-risk infants. However, the effects of PHFs on the developing gut microbiome are not known. METHODS: This study was a secondary analysis of the GLOWING study (ClinicalTrials.gov NCT01131117). Infant stool samples were collected at 6 months of age and microbial composition was examined via 16S rRNA amplicon sequencing (V4 region) using standardized methods. Samples were grouped by primary feeding type: Exclusive breastfeeding (BF; n = 42), IPF (n = 17), or PHF (n = 12). We used linear models to examine the effects of feeding type adjusting for lifetime breastfeeding exposure at 6 mo. Group differences in α-diversity (richness and diversity) and relative abundances were assessed by ANOVA or t-test. Between-specimen diversity (β-diversity) was assessed using Bray − Curtis dissimilarities. RESULTS: Total breast milk exposure did not differ between PHF and IPF (mean 32.3% of feeds from human milk, p = 0.08). Analysis of α-diversity showed higher evenness (Shannon, Simpson) in IPF and higher richness (Chao1, Observed OTU) in PHF. However, these differences were no longer significant after adjusting for breastmilk exposure. β-diversity did not differ between groups. At the genus level compared to BF, infants fed IPF had higher abundance of Parabacteroides, while those fed PHF had higher Erwinia and Clostridium. Peptostreptococcaceae family was also increased in PHF fed infants. Compared to IPF, the PHF group had higher abundance of Clostridium genus, and Peptostreptococcaceae and Enterobacteriaceae families. Elevated Enterobacteriaceae and Clostridiales have previously been found in children with food allergies. CONCLUSIONS: Our results suggest that partially hydrolyzed infant formulas may have modest impacts on the gut microbiome compared to intact protein formulas. Larger samples sizes are needed to fully characterize these differences and potential influence on long-term health. FUNDING SOURCES: U.S. Department of Agriculture, NIDDK.